Benefits of marine protected areas for tropical coastal sharks. Issue 6 (29th December 2015) - Yates, Peter M.; Tobin, Andrew J.; Heupel, Michelle R.; Simpfendorfer, Colin A.
Abstract: Coastal sharks face increasing pressure from anthropogenic impacts and environmental change. Estimated population declines in some species have created uncertainty about the effectiveness of existing management approaches. In particular, there are scarce data on the benefits of marine protected areas (MPAs) for sharks, including whether they can be used to conserve multiple sympatric species comprising diverse life histories and habitat use patterns. This study used fishery‐independent longline and gill‐net surveys to investigate the effects of sub‐bay‐sized MPAs ( c . 100–300 km 2 ) on the abundance and community structure of tropical coastal sharks. In addition, tag–recapture data from fishery‐dependent and fishery‐independent sources were used to investigate the movements of individuals across MPA boundaries. Species composition varied significantly between management zones, and overall shark abundance on longlines was higher inside MPAs. Length–frequency distributions of blacktip ( Carcharhinus tilstoni/Carcharhinus limbatus ) and pigeye ( Carcharhinus amboinensis ) sharks inside MPAs included a greater proportion of sharks larger than c . 800 mm compared with those in open zones, although results varied between gear types for pigeye sharks. Tagging and recapture locations indicated repeated and potentially long‐term use of MPAs by individuals of some species. Although the potential benefits of MPAs were not equal for all species, coastal MPAs may increase the survival of young sharks to maturity, or shelter parts of breeding stocks, and therefore do not necessarily need to be large to provide benefits. Copyright © 2015 John Wiley & Sons, Ltd.